TGF-β induces a heart failure phenotype via fibroblasts exosome signaling. Issue 10 (October 2019) - Basma, Hesham; Johanson, Adelaide N.; Dhar, Kajari; Anderson, Daniel; Qiu, Fang; Rennard, Stephen; Lowes, Brian D.
Abstract: Purpose: The mechanisms for persistent and progressive loss of myocardial function in advanced heart failure (HF) remain incompletely characterized. In the current study, we sought to determine the impact of TGF-β on fibroblasts transcriptional profiles and assess if exosomes from TGF-β treated fibroblasts could induce a heart failure phenotype in co-cultured cardiomyocytes. Method: Normal heart fibroblasts were treated with TGF-β with a final conc. of 2.5 ng/ml in serum free media. HF fibroblasts were also obtained from patients undergoing implantation of left ventricular assist devices. Exosomes were collected using three-step ultracentrifugation. Cardiomyocytes were co-cultured with exosomes from TGF-β-treated, HF and control fibroblasts. RNA was extracted from the fibroblasts, exosomes, and the cardiomyocytes for a targeted panel of genes using Ion AmpliSeq. Fibroblast function was evaluated by collagen gel contraction. Results: Fibroblasts treated with TGF-β differentially express 21 of the 140 genes in our targeted panel. These fibroblasts exhibit enhanced collagen gel contraction similar to HF fibroblasts. Fifty of these targeted genes were also differentially expressed in fibroblast exosomes. Pathway analysis of these transcriptional changes suggest hypertrophic signaling to cardiac muscle. Cardiomyocytes, co-cultured with exosomes from TGF- β treated fibroblasts or heart failure patients, differentially expressed 40 genes compared to controls. Cardiomyocytes co-cultured with exosomes of TGF-β treated fibroblasts induced a molecular phenotype similar to cardiomyocytes co-cultured with exosomes from HF fibroblasts. These changes involve contractile proteins, adrenergic receptors, calcium signaling, metabolism and cell renewal. Conclusion: TGF-β induces broad transcriptional changes in fibroblasts as well as their exosomes. These exosomes induce a heart failure phenotype in cardiomyocytes. Exosome signaling from fibroblasts likely contributes to disease progression in heart failure. Abstract : Cell biology; Biochemistry; Regenerative medicine; Oxidative stress; TGF-b; Heart failure; Exosomes